Pola Perilaku Masyarakat dalam Pengelolahan Limbah Rumah Tangga di Kecamatan Belawan Bahagia - Fitri Pramita Gurning; Serahayati Br Hasibuan; Cindi Ansari; Aseh Kumala Sari; Ayu Permata Sari; Azijah Nur Ismail (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The hygiene behavior studied is in the form of a series of various forms of behavior/actions that people take towards waste, including environmentally responsible behavior such as polluting the environment to responsible actions such as actions to maintain and clean the environment. In this article, the author uses quantitative research using a descriptive approach method to determine the relationship between community behavior and the way the community itself manages waste. The results of this study were obtained from filling in the introductory survey questionnaire which was changed to google form and asked to 95 people who were in the Belawan Bahagia area right in the 19th neighborhood.. Most respondents are male as much as 95.80% of respondents, most respondents' education is at the high school level as much as 36.8% and junior high school education is 35.8% and there are still respondents who have elementary education as much as. 23.2%, the most respondents in the village of Belawan Bahagia are fishermen as much as 54.7%. as much as 94.7% dispose of bathroom waste into the river/sea, this is because in the 19 village of Belawan Bahagia, almost most of the residents live in stilt houses built on the sea coast.